2017
DOI: 10.1038/s41598-017-11029-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Copy Number Variations and Gene Expression Profiling in Hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the top three cancer killers worldwide. To identify CNV-driven differentially expressed genes (DEGs) in HBV related HCC, this study integrated analysis of copy number variations (CNVs) and gene expression profiling. Significant genes in regions of CNVs were overlapped with those obtained from the expression profiling. 93 CNV-driven genes exhibiting increased expression in the duplicated regions and 45 showing decreased expression in the deleted regions were obtained, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 50 publications
4
23
0
1
Order By: Relevance
“…By data mining, we observed increased DNA copy number of Exo1 in HCC, in agreement with previous findings that the chromosomal region 1q, especially 1q42.12 and 1q43, has frequent copy number gains in more than 65% of HCC cases [32]. This finding prompted us to assess the expression levels of EXO1 in HCC, which remain unknown, since copy number variation (CNV) is an important genetic aberration and leads to the activation of oncogenes in cancer [33]. Moreover, a possible mechanism of chromosome abnormalities responsible for EXO1 gene upregulation other than modulation at the transcription and post-translation levels could be demonstrated [34,35].…”
Section: Discussionsupporting
confidence: 88%
“…By data mining, we observed increased DNA copy number of Exo1 in HCC, in agreement with previous findings that the chromosomal region 1q, especially 1q42.12 and 1q43, has frequent copy number gains in more than 65% of HCC cases [32]. This finding prompted us to assess the expression levels of EXO1 in HCC, which remain unknown, since copy number variation (CNV) is an important genetic aberration and leads to the activation of oncogenes in cancer [33]. Moreover, a possible mechanism of chromosome abnormalities responsible for EXO1 gene upregulation other than modulation at the transcription and post-translation levels could be demonstrated [34,35].…”
Section: Discussionsupporting
confidence: 88%
“…In accordance with our findings, previous studies have also identified DEGs that participate 320 in HBV-related liver cancer (Zhou et al, 2017). For example, Zhou et al analyzed the gene 321 expression profiles of GSE14520 and HCC samples from the Zhongshan Hospital affiliated with 322 Fudan University, which comprised 63 paired HCC and non-tumor samples.…”
supporting
confidence: 83%
“…In human, CNVs have been implicated in numerous diseases, such as autism and diabetes [ 12 , 13 ]. CNVs also contribute significantly to the genome instability of cancer cells [ 14 16 ]. For example, recently, Pelttari [ 14 ] reported a unique duplication encompassing most of the RAD51 homolog C gene in breast and ovarian cancers.…”
Section: Introductionmentioning
confidence: 99%